Augmented Reality Prototype for Visualising Large Sensors’ Datasets - Folorunso Olufemi A.; Mohd Shahrizal S. Mohd Shahrizal S.; Ikotun Abiodun M. (Universitas Ahmad Dahlan, 2011)
This paper addressed the development of an augmented reality (AR) based scientific visualization system prototype that supports identification, localisation, and 3D visualisation of oil leakages sensors datasets. Sensors generates significant amount of multivariate datasets during normal and leak situations which made data exploration and visualisation daunting tasks. Therefore a model to manage such data and enhance computational support needed for effective explorations are developed in this paper. A challenge of this approach is to reduce the data inefficiency. This paper presented a model for computing information gain for each data attributes and determine a lead attribute.The computed lead attribute is then used for the development of an AR-based scientific visualization interface which automatically identifies, localises and visualizes all necessary data relevant to a particularly selected region of interest (ROI) on the network. Necessary architectural system supports and the interface requirements for such visualizations are also presented.